Effects of Shiga toxin type 2 on maternal and fetal status in rats in the early stage of pregnancy - Sacerdoti, Flavia (2014)
Shiga toxin type 2 (Stx2), a toxin secreted by Shiga toxin-producing Escherichia coli (STEC), could be one of the causes of maternal and fetal morbimortality not yet investigated. In this study, we examined the effects of Stx2 in rats in the early stage of pregnancy. Sprague-Dawley pregnant rats were intraperitoneally (i.p.) injected with sublethal doses of Stx2, 0.25 and 0.5 ng Stx2/g of body weight (bwt), at day 8 of gestation (early postimplantation period of gestation). Maternal weight loss and food and water intake were analyzed after Stx2 injection. Another group of rats were euthanized and uteri were collected at different times to evaluate fetal status. Immunolocalization of Stx2 in uterus and maternal kidneys was analyzed by immunohistochemistry. The presence of Stx2 receptor (globotriaosylceramide, Gb3) in the uteroplacental unit was observed by thin layer chromatography (TLC). Sublethal doses of Stx2 in rats caused maternal weight loss and pregnancy loss. Stx2 and Gb3 receptor were localized in decidual tissues. Stx2 was also immunolocalized in renal tissues. Our results demonstrate that Stx2 leads to pregnancy loss and maternal morbidity in rats in the early stage of pregnancy.This study highlights the possibility of human pregnancy loss and maternal morbidity mediated by Stx2.